2018
DOI: 10.1002/cmdc.201800273
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3‐Triazolium‐Based Cationic Amphipathic Peptoid Oligomers Mimicking Antimicrobial Helical Peptides

Abstract: Amphipathic cationic peptoids (N-substituted glycine oligomers) represent a promising class of antimicrobial peptide mimics. The aim of this study is to explore the potential of the triazolium group as a cationic moiety and helix inducer to develop potent antimicrobial helical peptoids. Herein we report the first solid-phase synthesis of peptoid oligomers incorporating 1,2,3-triazolium-type side chains and their evaluation against Escherichia coli, Enterococcus faecalis, and Staphylococcus aureus. Several tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…[9] As a result, the majority of clinical applicable AMPs are used or designed for topical applications only with very few exceptions aimed for systematic applications. [5] To overcome these limitations, many different strategies, including but not limited to structural/ sequence modification, [10][11][12][13] specific delivery system design, [14][15][16][17] "smart" AMPs [18][19][20] and de novo designed antimicrobial peptides/peptidomimetics [21][22][23][24][25][26][27] have been developed to efficiently use AMPs without being hindered by their side-effects. Among these strategies, modification or mimicry of naturally occurring peptides with natural amino acids or unnatural building blocks is an efficient pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[9] As a result, the majority of clinical applicable AMPs are used or designed for topical applications only with very few exceptions aimed for systematic applications. [5] To overcome these limitations, many different strategies, including but not limited to structural/ sequence modification, [10][11][12][13] specific delivery system design, [14][15][16][17] "smart" AMPs [18][19][20] and de novo designed antimicrobial peptides/peptidomimetics [21][22][23][24][25][26][27] have been developed to efficiently use AMPs without being hindered by their side-effects. Among these strategies, modification or mimicry of naturally occurring peptides with natural amino acids or unnatural building blocks is an efficient pathway.…”
Section: Introductionmentioning
confidence: 99%
“…[94] Higher hydrophobization of peptoids does not always equate with potent activity and is dependent on the type of bacteria, such as Escherichia coli, Pseudomonas aeruginosa and S. aureus. [95] Cationic side chains such as the 1,2,3-triazolium-type [96] were used to develop antimicrobial peptoids. Faure and co-workers reported that the 1,2,3-triazolium moiety on various side-chain substituents alters activity and selectivity of the peptoids.…”
Section: Peptoidsmentioning
confidence: 99%
“…Following this mimicking trend, Shyam et al prepared a series of 1,2,3-triazolium-based cationic amphipathic peptoid oligomers that mimic antimicrobial helical peptides [ 190 ]. They explored the potential of the triazolium group as a cationic moiety and helix inducer to develop potent antimicrobial helical peptoids.…”
Section: Mimicking the Structure Of Ampsmentioning
confidence: 99%